Tensile, thermal degradation and water diffusion behaviour of gamma-radiation induced recycled polymer blend/rice husk composites: experimental and statistical analysis - Chen, Ruey Shan; Ab Ghani, Mohd Hafizuddin; Ahmad, Sahrim; Tarawneh, Mou'ad A.; Gan, Sinyee (Elsevier, 2021)
Bio-composites made from recycled polymers and rice husk fibers (RHF) were melt-compounded via extrusion and compression molding. The pressed composite panels were subjected to gamma radiation post-treatment. The effects of high fiber loadings (40–80 wt%) and gamma radiation doses (25–150 kGy) on the tensile, thermal and water uptake properties were examined. From the findings, the gamma radiation had improved the tensile properties and dimensional stability as indicated by the lower water absorption and thickness swelling for composites containing lower RHF loading. The maximum increment of 200% for modulus and about 15% for tensile strength and water absorption resistance was achieved at 40 wt% RHF with 50 kGy. At higher RHF loading, only the lower dose of 25 kGy gave the positive effect in tensile performance and water resistance. At 150 kGy, a failure in mechanical and thermal stability was observed which proved the adverse effect induced by high dose.